Effects of active versus passive recovery in sprint cross-country skiing - Losnegard, T.; Andersen, M.; Spencer, M.; Hallén, J. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To investigate the effects of an active and a passive recovery protocol on physiological responses and performance between 2 heats in sprint cross-country skiing. Methods: Ten elite male skiers (22 ± 3 y, 184 ± 4 cm, 79 ± 7 kg) undertook 2 experimental test sessions that both consisted of 2 heats with 25 min between start of the first and second heats. The heats were conducted as an 800-m time trial (6°, >3.5 m/s, ~205 s) and included measurements of oxygen uptake (VO2) and accumulated oxygen deficit. The active recovery trial involved 2 min standing/walking, 16 min jogging (58% ± 5% of VO2peak), and 3 min standing/walking. The passive recovery trial involved 15 min sitting, 3 min walk/jog (~ 30% of VO2peak), and 3 min standing/walking. Blood lactate concentration and heart rate were monitored throughout the recovery periods. Results: The increased 800-m time between heat 1 and heat 2 was trivial after active recovery (effect size [ES] = 0.1, P = .64) and small after passive recovery (ES = 0.4, P = .14). The 1.2% ± 2.1% (mean ± 90% CL) difference between protocols was not significant (ES = 0.3, P = .3). In heat 2, peak and average VO2 was increased after the active recovery protocol. Conclusions: Neither passive recovery nor running at ~58% of VO2peak between 2 heats changed performance significantly.